Treatment of resistant forms of systemic lupus erythematosus with a type I interferon inhibitor in the early access program - I. A. Leineman; R. R. Samigullina; M. S. Shostak; V. I. Mazurov (Современная ревматология)
The article presents the results of treatment of patients with systemic lupus erythematosus (SLE), who, due to resistance to traditional regimens, for the first time in the Russian Federation were included in the early access program of the type I interferon inhibitor – anifrolumab. Clinical data and results of instrumental examinations of a patient with SLE on the background of 6-month therapy are presented.